2019
DOI: 10.3390/cancers12010068
|View full text |Cite
|
Sign up to set email alerts
|

TCA Cycle Rewiring as Emerging Metabolic Signature of Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a common malignancy. Despite progress in treatment, HCC is still one of the most lethal cancers. Therefore, deepening molecular mechanisms underlying HCC pathogenesis and development is required to uncover new therapeutic strategies. Metabolic reprogramming is emerging as a critical player in promoting tumor survival and proliferation to sustain increased metabolic needs of cancer cells. Among the metabolic pathways, the tricarboxylic acid (TCA) cycle is a primary route for bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 165 publications
1
63
0
Order By: Relevance
“…Early studies suggested that cancer cells bypass the TCA cycle and use aerobic glycolysis, but emerging evidence suggests that some cancer cells, particularly those with the maladjusted expression of oncogenes and tumor suppressors, rely heavily on the TCA cycle to produce energy and synthesize large molecules [ 35 ]. In a variety of cancers, including HCC, the expression or activity levels of the TCA cycle and related enzymes are generally dysregulated, which is a pivotal driver of cancer development and progression [ 36 , 37 ]. In addition, wild-type P53 also has an important effect on metabolism, the mutation of P53 will lead to the enhancement of glycolysis and the reduction of oxidative phosphorylation in tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies suggested that cancer cells bypass the TCA cycle and use aerobic glycolysis, but emerging evidence suggests that some cancer cells, particularly those with the maladjusted expression of oncogenes and tumor suppressors, rely heavily on the TCA cycle to produce energy and synthesize large molecules [ 35 ]. In a variety of cancers, including HCC, the expression or activity levels of the TCA cycle and related enzymes are generally dysregulated, which is a pivotal driver of cancer development and progression [ 36 , 37 ]. In addition, wild-type P53 also has an important effect on metabolism, the mutation of P53 will lead to the enhancement of glycolysis and the reduction of oxidative phosphorylation in tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, liposomal HCA, by targeting immunometabolism through ACLY metabolic enzyme, could represent an innovative approach to many pathological conditions, since inflammation underlies countless diseases. Finally, as ACLY is also overexpressed in a wide variety of tumors, such as hepatocellular carcinoma [ 2 ], it is reasonable to suppose that liposomal HCA might be useful for the treatment of cancer, maybe in combination with other drugs.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has been discovered that metabolic shifts of activated macrophages, in many cases shared with cancer cells [ 2 ], also involve the Krebs cycle rewiring, leading to the accumulation of citrate, succinate, and fumarate [ 3 ]. In LPS- or TNFα/IFNγ-activated macrophages, the mitochondrial citrate carrier (CIC) exports citrate from the mitochondria to the cytosol where the ATP citrate lyase (ACLY) enzyme catalyzes its conversion into oxaloacetate (OAA) and acetyl-CoA.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies suggested that cancer cells bypass the TCA cycle and use aerobic glycolysis, but emerging evidence suggests that some cancer cells, particularly those with maladjusted expression of oncogenes and tumor suppressors, rely heavily on the TCA cycle to produce energy and synthesize large molecules (30). In a variety of cancers, including HCC, the expression or activity levels of the TCA cycle and related enzymes are generally dysregulated, which is a pivotal driver of cancer development and progression (31,32). In addition, wild-type P53 alos has an important effect on metabolism,the mutation of P53 will lead to the enhancement of glycolysis and the reduction of oxidative phosphorylation in tumor cells.…”
Section: Discussionmentioning
confidence: 99%